Learning Styles and Academic Learning Time as Predictors of Secondary School Students’ Achievement in Chemistry - Opateye, Johnson Ayodele (West African Journal of Open and Flexible Learning, 2026)
The study investigated learning styles and academic learning time as predictors of secondary students’ achievement in chemistry. Using an ex post facto research type, four research hypotheses were tested. Two instruments - Learning styles (r=0.76) and academic learning time (r= 0.78) questionnaire (LSALTQ) and Chemistry Achievement Test (EAT) (r= 0.81) were used to gather data. Two hundred and forty chemistry students were randomly selected from four Local Government Areas of Oyo State, Nigeria. Multiple regression analysis was used to analyse the data. The results showed that there was a significant composite contribution of learning styles (lesson structure, sociological, auditory and tactile) and chemistry academic earning time available ( allocated, instructional, engaged) to students’ achievement in chemistry. Lesson structure had a relatively significant contribution to determining the achievement of students in chemistry. Teacher instructional time had the highest contribution followed by students’ engaged time. Chemistry teachers need to adapt their instructional delivery to the different learning styles of the students. Sufficient instructional and student-engaged times should be available for teaching, learning and laboratory practical activities. More time is to be devoted to students’ learning while non-academic-related activity times that consume the learning time should be drastically reduced.